Chemically refined high-strength cement grouting material as well as preparation method and application thereof

Through chemical refinement methods, combined with nano-modification and dissolution-nuclear effect, prepare high-intensity and good mushability grouting materials, solve the lack of traditional cement grouting materials in deep rock body grouting, and achieve efficient , Stable and low grouting effect.

CN119330663APending Publication Date: 2025-01-21CHINA UNIV OF MINING & TECH
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411443819.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-16
Publication Date
2025-01-21

AI Technical Summary

Technical Problem

Traditional cement grouting materials have problems such as poor injectability, slow strength development, high energy consumption, low fluidity, poor volume stability and deterioration of moisture absorption of fine-grain cement in deep-ground environments in deep-ground environments, which are difficult to meet the deep-ground Engineering requirements.

Method used

Through chemical refinement method, ordinary Portland cement, fly ash, nano-silica, water reducing agent and activator are used, combined with nano-modification and dissolution-nucleation, to prepare high-strength and good-fluidity injection molding materials. pulp material.

Benefits of technology

It significantly improves the early strength, injectability and compactness of grouting materials, reduces production costs, simplifies the preparation process, and is suitable for the working conditions of deep underground engineering.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119330663A_ABST
    Figure CN119330663A_ABST
Patent Text Reader

Abstract

The invention discloses a chemically refined high-strength cement grouting material as well as a preparation method and application thereof, and belongs to the technical field of geotechnical engineering. The chemically refined high-strength cement grouting material is prepared from the following raw materials in parts by weight: 300 to 500 parts of cement, 50 to 150 parts of fly ash, 2.5 to 5 parts of nano silicon dioxide, 5 to 10 parts of a water reducing agent, 0 to 10 parts of an activating agent and 200 to 400 parts of water, wherein the weight part of the activating agent is not 0. According to the invention, the activator is used for accelerating the dissolution, decomposition and hydration of cement particles, and the early strength of the finally prepared grouting material is greatly improved in cooperation with nano-modification and dissolution-nucleation; the preparation method is simple and easy to implement and low in energy consumption, the production cost is reduced, and industrial production of the grouting material is promoted.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of geotechnical engineering, and in particular relates to a chemically refined high-strength cement grouting material and a preparation method and application thereof. Background Art

[0002] Mineral resources are related to the development of the national economy and the lifeline of national security. Shallow underground resources are becoming increasingly depleted, and mineral resource development is shifting from shallow to deep in the earth. Due to the large excavation depth and complex local geological structure, micro-cracks in the high-stress surrounding rock develop significantly during deep mining, and the damage of micro-cracks to the surrounding rock gradually becomes apparent. The existence of these micro-cracks greatly affects the strength, stability and sealing of deep rock mass, and becomes a potential hazard to the sustainable development of deep mineral resources. Micro-crack grouting reinforcement technology is a key technology to enhance the stability of surrounding rock, prevent rock deformation and damage, and construct safe underground space. The applicability of grouting materials and their mechanical properties play a decisive role in the anti-seepage effect of rock grouting reinforcement.

[0003] Ordinary cement has poor injectability in micro-crack grouting due to its large particles and agglomeration of particles during hydration. At the same time, due to its slow strength development, it is difficult to meet the engineering needs in the high ground stress environment of deep earth engineering. Therefore, ultrafine cement is used instead of ordinary cement in engineering. Ultrafine cement is made by grinding ordinary cement. Its production cycle is long, subsequent processing is complicated, and the cost is high. In addition, due to its fine particles, the slurry absorbs a large amount of water, which will cause the disadvantages of reduced fluidity and poor volume stability. In addition, the deep underground working conditions are complicated, and fine-grained cement is easy to weather and absorb moisture during storage. Various factors make it difficult for traditional grouting materials to play their role, and their application in deep earth engineering is limited.

[0004] At present, fine cement particles obtained by physical grinding are often used for grouting in engineering projects, which has solved the problem of poor injection rate of ordinary cement slurry in micro-cracks due to large particles. Although the injection effect of the slurry has been improved, it also leads to a series of problems caused by fine particles. Ultrafine cement particles are finer and have a larger specific surface area. In order to ensure fluidity when preparing slurry, a larger water-cement ratio is required, which will inevitably cause the particles to settle too quickly and the slurry to precipitate water. At the same time, due to the violent hydration reaction of ultrafine cement, the volume changes greatly during the solidification process, which seriously affects its stone strength and reinforcement effect. In deep earth engineering, fine cement grouting materials have to be mixed with various admixtures and auxiliary cementitious materials, which greatly increases the production cost.

[0005] In summary, there is an urgent need to provide an efficient, stable, and low-cost high-performance grouting material to improve the shortcomings of traditional grouting materials in deep fissure grouting, so as to improve the stability of deep rock masses and ensure the safety and stability of deep rock grouting projects. Summary of the invention

[0006] In response to the above technical problems, the present invention innovatively proposes a chemical refinement method for cement particles and develops a chemically refined high-strength cement grouting material to address the shortcomings of traditional cement grouting materials. This method only requires the use of ordinary Portland cement, and accelerates the dissolution, decomposition and hydration of cement particles through an activator, greatly reducing the particle size of cement particles and improving their fluidity, and then combining nano-modification and dissolution-nucleation to greatly improve the early strength of the grouting material; in addition, the present invention also solves the problems of high energy consumption, low fluidity, poor volume stability, moisture absorption and deterioration of fine-particle cement in deep underground environments, and hydration heat damage in existing fine-particle cement grouting materials; at the same time, it greatly reduces production costs and responds to the current sustainable development strategy.

[0007] To achieve the above object, the present invention provides the following technical solutions:

[0008] One of the technical solutions of the present invention:

[0009] A chemically refined high-strength cement grouting material, comprising the following raw materials in parts by weight:

[0010] 300-500 parts of cement, 50-150 parts of fly ash, 0-5 parts of nano-silicon dioxide, 5-10 parts of water reducer, 0-10 parts of activator and 200-400 parts of water;

[0011] Wherein, the dosage of the activator is not 0.

[0012] Preferably, the chemically refined high-strength cement grouting material comprises the following raw materials in parts by weight:

[0013] 300-500 parts of cement, 50-150 parts of fly ash, 2.5-5 parts of nano-silicon dioxide, 5-10 parts of water reducer, 0-10 parts of activator and 200-400 parts of water;

[0014] Wherein, the dosage of the activator is not 0.

[0015] Preferably, the cement is PO42.5 cement;

[0016] The water reducer is a polycarboxylic acid water reducer;

[0017] The activator is glacial acetic acid, which is AR analytical grade and has a content of not less than 99.5%.

[0018] Beneficial effects: The present invention limits glacial acetic acid as an activator, on the one hand because it is low in cost, easy to prepare, and low in toxicity among carboxylic acids, and therefore has the characteristics of green economy. On the other hand, because glacial acetic acid is a small molecular acid, it avoids the problems of other large molecular carboxylic acids (such as citric acid, tannic acid, etc.) that have strong complexation with calcium ions in cement slurry due to their large molecular weight, which will delay or even limit the strength development of grouting materials.

[0019] Preferably, the fly ash is secondary fly ash with a density of 2.4 g / cm 3 .

[0020] Preferably, the nano-silicon dioxide is hydrophilic, spherical particles, with a particle size of 15-20nm and a specific surface area of ​​300±50m 2 / g.

[0021] Preferably, the chemically refined high-strength cement grouting material comprises the following raw materials in parts by weight:

[0022] 450 parts of cement, 50 parts of fly ash, 2.5 parts of nano-silicon dioxide, 5 parts of water reducer, 5-10 parts of activator and 240-245 parts of water.

[0023] The second technical solution of the present invention:

[0024] A method for preparing a chemically refined high-strength cement grouting material comprises the following steps:

[0025] Weigh the weight of the raw materials for later use;

[0026] The nano-silicon dioxide, water reducing agent, activator and water are stirred at a low speed to obtain a mixed slurry;

[0027] Cement and fly ash are added to the mixed slurry and stirred at high speed to obtain chemically refined high-strength cement grouting material.

[0028] Preferably, the parameters during the low-speed stirring process are: stirring at a rotation speed of 300 rpm for 2 min.

[0029] Preferably, the high-speed stirring is overall high-speed stirring or graded high-speed stirring.

[0030] Preferably, the specific steps of the overall high-speed stirring are:

[0031] The slurry containing cement and fly ash was stirred at a rotation speed of 500 rpm for 3 minutes to obtain a grouting material.

[0032] Preferably, the specific steps of the graded high-speed stirring are:

[0033] First, add PO42.5 cement to the mixed slurry, and then stir at a speed of 500 rpm for 5 minutes;

[0034] Then, fly ash was added and stirred at a rotation speed of 500 rpm for 2 minutes to obtain a grouting material.

[0035] The third technical solution of the present invention:

[0036] The above-mentioned chemically refined high-strength cement grouting material is used in deep rock grouting projects.

[0037] Compared with the prior art, the present invention has the following advantages and technical effects:

[0038] The invention uses PO42.5 cement and fly ash, with activator (acetic acid) and nano-silicon dioxide. The innovation lies in that the activator is added during the mixing process, and the acid radical ions act as good proton receptors to react with the Ca in the cement particles. 2+ It has very good affinity and can accelerate the dissolution, decomposition and hydration speed of particles, thus refining the particles and solving the problem of poor injectability of PO42.5 cement. At the same time, nano-silica is used as a nano-hydration nucleation site to form a "dissolution-nucleation" synergistic effect with the activator, accelerating the generation of hydration products to achieve structural densification, greatly improving the strength and plugging effect of the slurry;

[0039] In addition, the present invention uses a small amount of raw materials to prepare a grouting material with high early strength, good fluidity, strong injectability, and high stone body density; and the preparation method of the present invention is simple and easy to implement, and the preparation is green and environmentally friendly, which can meet the sustainable and industrialized production requirements;

[0040] Furthermore, the present invention significantly shortens the preparation time of the grouting material, saves time and resources, and improves production efficiency and production benefits. BRIEF DESCRIPTION OF THE DRAWINGS

[0041] The drawings constituting a part of the present application are used to provide a further understanding of the present application. The illustrative embodiments and descriptions of the present application are used to explain the present application and do not constitute an improper limitation on the present application. In the drawings:

[0042] Figure 1 This is the hydration mechanism diagram when no active agent and nano-silicon dioxide are added;

[0043] Figure 2 This is a diagram of the hydration mechanism with the addition of active agents and nano-silicon dioxide;

[0044] Figure 3 It is a particle size distribution curve diagram of the grouting materials prepared in Examples 1-4 and Comparative Example 1;

[0045] Figure 4The pore distribution (3d) diagram of the grouting materials prepared in Examples 1-4 and Comparative Example 1;

[0046] Figure 5 This is the SEM (3d) image of the grouting materials prepared in Examples 1-4 and Comparative Example 1. DETAILED DESCRIPTION

[0047] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.

[0048] It should be understood that the terms described in the present invention are only for describing special embodiments and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. Each smaller range between the intermediate value in any stated value or stated range and any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.

[0049] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.

[0050] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to those skilled in the art. The present invention description and examples are exemplary only.

[0051] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.

[0052] The invention discloses a chemically refined high-strength cement grouting material, wherein the raw materials include, by weight: 300-500 parts of cement (model 42.5), 50-150 parts of fly ash, 2.5-5 parts of nano silicon dioxide, 5-10 parts of polycarboxylic acid high-efficiency water reducing agent, 0-10 parts of activator, and 200-400 parts of water;

[0053] Wherein, the weight fraction of the activator is not 0.

[0054] In some preferred embodiments, the raw materials of the chemically refined high-strength cement grouting material include cement, fly ash, water, nano-silicon dioxide, a water reducer and an activator; the raw materials are calculated in parts by weight:

[0055] 300-500 parts of cement, 50-150 parts of fly ash, 5-10 parts of water reducing agent, 200-400 parts of water, 0.56wt.% of nano-silicon dioxide content of the cement, 1-2wt.% of the activator content of the cementitious material (fly ash and cement). If the amount of the activator is higher than the amount range defined in the present invention, the strength at a later stage (28d) will be reduced.

[0056] In some more preferred embodiments, each raw material is calculated by weight:

[0057] 450 parts of cement, 50 parts of fly ash, 5 parts of water reducing agent, 240-245 parts of water, 0.56wt.% of nano silicon dioxide content of the cement, and 1-2wt.% of the activator content of the cementitious material (fly ash and cement).

[0058] In some preferred embodiments, the fly ash is secondary fly ash with a density of 2.4 g / cm 3 ;

[0059] Nano-silicon dioxide is hydrophilic, spherical particles with a particle size of 15-20nm and a specific surface area of ​​300±50m 2 / g;

[0060] The activator is glacial acetic acid (AR analytical grade, content not less than 99.5%).

[0061] The present invention also discloses a method for preparing a chemically refined high-strength cement grouting material, comprising the following steps:

[0062] First, the activator, nano-silica, water reducer and water were mixed at a speed of 300 rpm;

[0063] Then cement and fly ash are added in sequence and stirred at a rotation speed of 500 rpm to obtain a grouting material; the grouting material has the advantages of high early strength, good fluidity, strong injectability and high stone body density.

[0064] In summary, on the one hand, the grouting material prepared by the present invention solves the shortcomings of coarse ordinary silicate cement particles, poor injectability and slow strength development (compared with ordinary silicate cement grouting materials); it also solves the problems of high energy consumption, low fluidity, poor volume stability, moisture absorption and deterioration of fine-grained cement in deep underground environments, and hydration heat damage (compared with grinding ultrafine silicate cement grouting materials). That is, the present invention discloses a chemically refined high-strength cement grouting material, which has the characteristics of refined cement particles and high early strength, and has lower cost and higher construction efficiency, realizing the green and low-carbonization of deep underground grouting materials.

[0065] On the other hand, from an engineering perspective, the present invention abandons the use of ultra-fine cement, which is complicated to prepare and expensive, for deep grouting reinforcement, and instead uses a new type of efficient, stable and low-cost slurry material, whose performance is more in line with the working conditions of deep underground mining and is beneficial to improving the stability of deep rock masses.

[0066] The "parts" described in the present invention, unless otherwise specified, refer to parts by mass.

[0067] The raw materials used in the present invention are all purchased from the market.

[0068] The technical solution of the present invention is further illustrated by the following embodiments.

[0069] Example 1 (Activator content 1.0wt.%, no nanomaterial added, wherein the activator content is the mass percentage of the cementitious material (fly ash and cement), the same below)

[0070] A method for preparing a chemically refined high-strength cement grouting material comprises the following steps:

[0071] First, polycarboxylate superplasticizer (5 parts), glacial acetic acid (5 parts) and water (245 parts) were mixed at a rotation speed of 300 rpm for 2 minutes to obtain a mixture;

[0072] The mixture was then stirred with PO42.5 cement (450 parts) and fly ash (50 parts) at a rotation speed of 500 rpm for 3 minutes to obtain a grouting material.

[0073] Example 2 (Activator content 1.0wt.%, nanomaterial added)

[0074] First, nano-silica (2.5 parts), polycarboxylic acid high-efficiency water reducer (5 parts), glacial acetic acid (5 parts) and water (245 parts) were mixed at a rotation speed of 300 rpm for 2 minutes to obtain a mixture;

[0075] The mixture was then stirred with PO42.5 cement (450 parts) and fly ash (50 parts) at a rotation speed of 500 rpm for 3 minutes to obtain a grouting material.

[0076] Example 3 (Activator content 1.0wt.%, nanomaterials, activation time (and second step of separate stirring) increased)

[0077] First, nano-silica (2.5 parts), polycarboxylic acid high-efficiency water reducer (5 parts), glacial acetic acid (5 parts) and water (245 parts) were mixed at a rotation speed of 300 rpm for 2 minutes to obtain a mixture;

[0078] The mixture was then stirred with PO42.5 cement (450 parts) at a rotation speed of 500 rpm for 5 minutes; and then stirred with fly ash (50 parts) at a rotation speed of 500 rpm for 2 minutes to obtain a grouting material.

[0079] Example 4 (Activator content 2.0wt.%, nanomaterials, activation time (and second step of separate stirring) increased)

[0080] First, nano-silicon dioxide (2.5 parts), polycarboxylic acid high-efficiency water reducer (5 parts), glacial acetic acid (10 parts) and water (240 parts) were mixed at a rotation speed of 300 rpm for 2 minutes to obtain a mixture;

[0081] The mixture was then stirred with PO42.5 cement (450 parts) at a rotation speed of 500 rpm for 5 minutes; and then stirred with fly ash (50 parts) at a rotation speed of 500 rpm for 2 minutes to obtain a grouting material.

[0082] Comparative Example 1: Ordinary Portland Cement

[0083] The difference from Example 1 is that no activator is added and the amount of water is increased to 250 parts. The preparation steps of the ordinary Portland cement are:

[0084] First, polycarboxylate superplasticizer (5 parts) and water (250 parts) were mixed at a rotation speed of 300 rpm for 2 min to obtain a mixture;

[0085] The mixture was then mixed with PO42.5 cement (450 parts) and fly ash (50 parts), and stirred at 500 rpm for 3 minutes to obtain a grouting material.

[0086] Effect verification

[0087] The performance of the grouting materials prepared in the above-mentioned Examples 1-4 and Comparative Example 1 is now tested, and the specific test effect data are shown in Table 1.

[0088] Table 1

[0089]

[0090] As shown in Table 1, the difference between Example 2 and Example 1 is that nanomaterials are added in Example 2, and the particle size, average pore size and viscosity of the prepared grouting material are all reduced, the compressive strength is improved, and the overall performance of the grouting material is improved, indicating that nano silicon dioxide has a certain synergistic effect with the activator during the grouting process, which is conducive to improving the working performance and mechanical properties of the slurry; it can be seen from the grouting material performance of Example 4 and Example 3 that as the amount of activator added increases, the particle size, viscosity and average pore size of the grouting material are promoted, and the compressive strength is improved. And by comparing with Example 2, it can be seen that the extension of the activation time is also conducive to improving the working performance and mechanical strength of the grouting material.

[0091] Figure 1 is the hydration mechanism diagram when no active agent and nano-silicon dioxide are added; Figure 1 It can be seen that when no activator is added, hydration products begin to form on the surface of cement particles after contact with water, and the dissolution of particles is hindered, which hinders further hydration reaction. Therefore, there will be many cement particles that have not completed the hydration reaction.

[0092] Figure 2 The diagram is a hydration mechanism diagram with the addition of active agent and nano-silicon dioxide; Figure 2 It can be seen that after adding the activator, the hydration products on the surface begin to dissolve under the action of the activator, enter the solution in the form of ions, and re-nucleate on the surface of the nano-silica, making the particles refined.

[0093] Figure 3 is a particle size distribution curve of the grouting materials prepared in Examples 1-4 and Comparative Example 1; Figure 3 It can be seen that there are many particles larger than 100 μm in the ordinary Portland cement grouting material of Comparative Example 1, but with the addition of activator and the extension of activation time, the number of particles larger than 100 μm is significantly reduced, and the refining effect of coarse particles can reach more than 40%.

[0094] Figure 4 The pore distribution (3d) diagram of the grouting materials prepared in Examples 1-4 and Comparative Example 1; Figure 4 It can also be seen that with the addition of the activator and the extension of the activation time, the pores with a size of about 1000 nm inside the grouting stone body begin to transform into pores of about 100 nm, and the average pore size decreases from 36.63 nm in comparative example 1 to a minimum of 26.69 nm (see Table 1 for details), and the degree of pore densification increases by more than 25% (e.g., (36.63-26.69) / 36.63=27.14%), and the overall density far exceeds that of ordinary silicate cement grouting material, indicating that it has better grouting reinforcement and plugging capabilities.

[0095] Figure 5 The SEM (3d) images of the grouting materials prepared in Examples 1-4 and Comparative Example 1 are shown in FIG. Figure 5 (a) is a microscopic morphology of comparative example 1. It can be seen from the figure that the growth of the hydration product is very slow and the density is low. The morphology of the hydrated calcium silicate gel is mainly irregular cluster shape. Figure 5 (b)- Figure 5 (e) are microscopic morphology images of Examples 1-4. Figure 5 As can be seen in (b), after adding the activator, the density of the hydration product increases, and the needle-shaped calcium silicate hydrate gel grows in the pores, playing a bridging and filling role, which corresponds well to Figure 4 The reduction of porosity in Figure 5 In (c)-(e), due to the nucleation effect of the nanomaterials, a large amount of fibrous network-like calcium silicate hydrate is formed, and its density continues to increase with the increase of activation dosage and the extension of activation time. Figure 5 (f) Figure 5 (e) is a partial enlarged view, in which the hydration products of flaky calcium hydroxide and fly ash surfaces can be clearly seen. A large number of hydration products are formed in the pores and cross-linked with each other. The micropores are well filled, greatly improving the density of the grouting material.

[0096] The above are only preferred specific implementations of the present application, but the protection scope of the present application is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed in the present application should be included in the protection scope of the present application. Therefore, the protection scope of the present application should be based on the protection scope of the claims.

Claims

1. A chemically refined high-strength cement grouting material, characterized in that: According to weight parts, it includes the following raw materials: 300-500 parts of cement, 50-150 parts of fly ash, 0-5 parts of nano-silicon dioxide, 5-10 parts of water reducer, 0-10 parts of activator and 200-400 parts of water; Wherein, the weight fraction of the activator is not 0.

2. A chemically refined high-strength cement grouting material according to claim 1, characterized in that: The activator is glacial acetic acid.

3. The chemically refined high-strength cement grouting material according to claim 1, characterized in that: The nano-silicon dioxide is hydrophilic, with a particle size of 15-20nm and a specific surface area of ​​300±50m 2 / g.

4. The chemically refined high-strength cement grouting material according to claim 1, characterized in that: The chemically refined high-strength cement grouting material comprises the following raw materials in parts by weight: 450 parts of cement, 50 parts of fly ash, 2.5 parts of nano-silicon dioxide, 5 parts of water reducer, 5-10 parts of activator and 240-245 parts of water.

5. A method for preparing a chemically refined high-strength cement grouting material, characterized in that: The following steps are involved: Weigh the weight of the raw material according to any one of claims 1 to 4 for later use; The nano-silicon dioxide, water reducing agent, activator and water are stirred at a low speed to obtain a mixed slurry; Cement and fly ash are added to the mixed slurry and stirred at high speed to obtain chemically refined high-strength cement grouting material.

6. The method for preparing a chemically refined high-strength cement grouting material according to claim 5, characterized in that: The parameters during the low-speed stirring process are: Stir at 300 rpm for 2 min.

7. The method for preparing a chemically refined high-strength cement grouting material according to claim 5, characterized in that: The high-speed stirring is overall high-speed stirring or graded high-speed stirring.

8. The method for preparing a chemically refined high-strength cement grouting material according to claim 7, characterized in that: The specific steps of the overall high-speed stirring are: The slurry containing cement and fly ash was stirred at a rotation speed of 500 rpm for 3 minutes to prepare a grouting material.

9. The method for preparing a chemically refined high-strength cement grouting material according to claim 7, characterized in that: The specific steps of the graded high-speed stirring are: Firstly, cement was added into the mixed slurry, and then stirred at a speed of 500 rpm for 5 minutes; Then, fly ash was added and stirred at a rotation speed of 500 rpm for 2 minutes to obtain a grouting material.

10. Use of the chemically refined high-strength cement grouting material according to any one of claims 1 to 4 in deep rock mass grouting engineering.

Citation Information

Cited By

  • Composition for wet-ground cement-based nano-composite grouting material, wet-ground cement-based nano-composite grouting material as well as preparation method and application of wet-ground cement-based nano-composite grouting material

    CN119774968A